Development of core outcome set for healthy aging treatment in primary care settings - Soobin Jang; Hyein Jeong; Jungi Park; Mi Mi Ko; Jeeyoun Jung (Integrative Medicine Research)
Background: Healthy aging is a global public health priority, with increasing interest in the promotion of functional ability and well-being among older adults. South Korea’s rapidly aging population highlights the need for standardized evaluation tools for interventions. This study aimed to develop a Core Outcome Set (COS) for healthy aging treatment in primary care. Methods: The COS was developed following the COS-STAD guidelines and through a multiphase process, including a literature review and a modified Delphi consensus. A project management group (PMG) reviewed studies related to health promotion programs and generated an initial list of outcomes. This list was refined through two rounds of Delphi surveys involving 16 experts. Consensus was assessed using content validity ratio, degree of consensus, and convergence. Results: Twenty-six studies informed the initial outcome list, resulting in 24 outcomes for the Delphi evaluation. Two Delphi rounds and a final review by the PMG established a COS comprising 12 outcomes. These included EQ-5D, Geriatric Depression Scale, Instrumental Activities of Daily Living, body weight, blood pressure, blood glucose, blood lipids, liver function, kidney function, Korean Frailty Index, Self-rated Health, and Kidney-Deficiency Score. Conclusions: The COS provides a standardized set of outcomes for evaluating healthy aging interventions in primary care. Its application in primary care and health promotion programs may enhance comparability across studies and support evidence-based decision making. Future revisions are recommended based on clinical applications and emerging research findings.